European Union’s solutions to domain names on the internet - Özgür, Didem (My University, 2003)
İnternetin gelişmesiyle birlikte alan isimleri teknik özelliklerinden daha çok tanıtıcı fonksiyonlarıyla gündeme gelmişlerdir.Bu çalışmanın amacı marka hukuku ve alan isimleri arasında yaşanan problemleri araştırmaktı.Marka sahipleri markalarını daha önceleri geleneksel marka hukuku kuralları,haksız rekabet kurallarıyla koruyabilmekteydiler.İnternetin ve teknolojinin gelişmesiyle birlikte bu konudaki hukuki çalışmalar yetersiz ve statik kalmıştır.Marka sahiplerinin siber ortamda haklarını koruyabilmek için bir çok ulusal ve uluslararası çalışmalar yapılmıştır.Yeknesak Uyuşmazlık Çözüm Mekanizması bu çalışmaların başında gelmektedir.Diğer taraftan her ülke kendi ulusal mevzuatını internet alan isimleri ve markalar arasında yaşanan problemleri çözmek için değiştirmeye ve uyumlaştırmaya başlamıştır.Bu çalışmalar marka sahiplerinin haklarını belli bir dereceye kadar koruyabilmektedir.Devletler, her ne kadar İnternet ortamında kanun yapmak zor olsa da yaşanan bu problemleri çözmek için toplanmalı ve yeni uluslararası kurallar oluşturmalıdır.Yapılan bu reformlar markalar konusunda yaşanan problemleri azaltsa da yakın zamanda markalar ve alan isimleri arasında yaşanan sorunların tamamen ortadan kalkacağı sanılmamaktadır.İnternet eğer bu düzeyde ticarileşmeye devam ederse alan isimleri hukukumarkalar hukukunun özel bir alanı olarak gelecekte önemini koruyacaktır. As the Internet has been developed domain names have become more important for their technical functions but also for their identification functions.The purpose of this study is to examinetrademark and domain name problems seen in the newly devoloping Internet law.In the past trademark owners protected their trademarks using traditional trademark legislations or unfair competition rules.However as the Internet and technology started to grow faster,legal arrangements about these issues remained static and insufficient.Many national and international improvements have been made to protect trademark owners' rights in the cyberspace.Uniform Dispute Resolution Mechanism is on of the leading improvements about this matter.On the other side each country started to implement its own national legislation to solve these problems.These applications protect trademark owners' rights to some extent.The International Community must gather to solve their problems and diffrences about Internet domain names by creating new international norms,however,regulation is very difficult in the cyberspace.Although the intended reforms might help in minimizing some of the trademark issues,it can still not be assumed that in the near future most of the conflict situations between trademarks and domain names will fade into insignificance.If the commercialization of the Internet continues of the current pace the law of domain names as a specific sector of trademark law will play an important role in the future legal practice.
Keywords: Avrupa Birliği